Acculturation in the Integration Course for Immigrants in Germany: A Study from the Cultural Bridge Approach - Tovar-Gálvez, Julio César (Journal of Ethnic and Cultural Studies, 2022)
Acculturation processes as inclusive cultural interactions may or may not be motivated by educational contexts. This paper studies the acculturation process in the integration course that the German government offers to hundreds of thousands of immigrants. The framework is the Cultural Bridge (CB) that happens when individuals or communities participate in diverse cultures while preserving their own culture. The method is the content analysis of semi-structured interviews. Six immigrants provide information about their experience in the integration course. The results show approaches to and limitations for cultural inclusion. Finally, the discussion interprets the findings from the CB, compares this study with other results and presents some implications. In conclusion, the integration course leads to partially inclusive acculturation processes.